A molecular survey of canine respiratory viruses in New Zealand. Issue 4 (26th May 2021) - More, GD; Cave, NJ; Biggs, PJ; Acke, E; Dunowska, M
ABSTRACT: Aims: The aim of this study was to identify viruses associated with canine infectious respiratory disease syndrome (CIRDS) among a population of New Zealand dogs. Methods: Convenience samples of oropharyngeal swabs were collected from 116 dogs, including 56 CIRDS-affected and 60 healthy dogs from various locations in New Zealand between March 2014 and February 2016. Pooled samples from CIRDS-affected (n = 50) and from healthy (n = 50) dogs were tested for the presence of canine respiratory viruses using next generation sequencing (NGS). Individual samples (n = 116) were then tested by quantitative PCR (qPCR) and reverse transcriptase qPCR (RT-qPCR) for specific viruses. Groups were compared using Fisher's exact or χ 2 tests. The effect of explanatory variables (age, sex, type of household, presence of viral infection) on the response variable (CIRDS-affected or not) was tested using RR. Results: Canine pneumovirus (CnPnV), canine respiratory coronavirus (CRCoV), canine herpesvirus-1 (CHV-1), canine picornavirus and influenza C virus sequences were identified by NGS in the pooled sample from CIRDS-affected but not healthy dogs. At least one virus was detected by qPCR/RT-qPCR in 20/56 (36%) samples from CIRDS dogs and in 23/60 (38%) samples from healthy dogs (p = 0.84). CIRDS-affected dogs were most commonly positive for CnPnV (14/56, 25%) followed by canine adenovirus-2 (CAdV-2, 5/56, 9%), canine parainfluenza virus (CpiV) and CHV-1 (2/56, 4% each), and CRCoV (1/56, 2%). Only CnPnV (17/60, 28%) and CAdV-2 (14/60, 23%) were identified in samples from healthy dogs, and CAdV-2 was more likely to be detected healthy than diseased dogs (RR 0.38; 95% CI = 0.15–0.99; p = 0.045) Conclusions: The frequency of detection of viruses traditionally linked to CIRDS (CAdV-2 and CPiV) among diseased dogs was low. This suggests that other pathogens are likely to have contributed to development of CIRDS among sampled dogs. Our data represent the first detection of CnPnV in New Zealand, but the role of this virus in CIRDS remains unclear. On-going monitoring of canine respiratory pathogens by NGS would be beneficial, as it allows rapid detection of novel viruses that may be introduced to the New Zealand canine population in the future. Such monitoring could be done using pooled samples to minimise costs. Clinical relevance: Testing for novel respiratory viruses such as CnPnV and CRCoV should be considered in all routine laboratory investigations of CIRDS cases, particularly in dogs vaccinated with currently available kennel cough vaccines.